Graphdiyne modified lithium iron phosphate composite positive electrode material and preparation method thereof
Through the method of combining high -temperature sintering with the graphite 炔 compound with oxygen -containing groups, the lithium iron phosphate orthopedic material is solved, and the problem of low conductivity and limited electrochemical properties have been solved. stability.
Patent Information
- Application Number
- CN202411491855.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have low conductivity, easy particles to agglomerate, high surfactant cost, and complex solid-liquid separation process, resulting in limited electrochemical performance.
The lithium iron phosphate is prepared by solid -phase synthesis, and then compounded with the graphite of oxygen -containing groups, which is closely integrated through high temperature sintering to form a high -performance positive electrode material.
The charging and discharge ratio and cycle stability of the lithium -ion battery are significantly improved, and the material shows excellent conductivity and mass transfer efficiency during the battery filling process.
Smart Images

Figure CN119361644A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to a composite positive electrode material of graphyne-modified lithium iron phosphate and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, and portability, and are widely used in various energy storage fields. The performance of lithium-ion batteries depends largely on their cathode materials. Lithium iron phosphate has become one of the main cathode materials for commercial lithium-ion batteries due to its large theoretical specific capacity, good cycle stability, low price and environmental protection. However, due to the low conductivity between lithium iron phosphate particles, easy agglomeration of particles, high cost of surfactants, and complex solid-liquid separation process, the electrochemical performance is very limited. Modifying it is the most effective strategy to improve the electrochemical performance.
[0003] my country's lithium iron phosphate industry has gradually become complete and mature, and it has become the only country in the world that integrates large-scale research and development and commercial applications. In recent years, scientific researchers have functionalized lithium iron phosphate through coating, doping, particle nano-sizing, morphology control and other means, making it have good applications in new energy vehicle power batteries, starting power supplies, energy storage systems and other fields. Improving electronic conductivity and lithium ion migration rate will help improve the charging and discharging performance of lithium iron phosphate materials under high power, which is the main technical approach to the development of fast charging technology. Among the many conductive additives, graphene has attracted widespread attention from researchers due to its good conductivity and unique molecular structure. However, graphene has a dense six-membered ring structure that lithium ions cannot penetrate and can only diffuse within the surface, making the performance of graphene-modified lithium iron phosphate less than ideal.
[0004] Glydne not only has higher conductivity than graphene, but also has a large pore structure, which is conducive to the rapid diffusion of lithium ions between layers, and has great application potential in the modification of lithium iron phosphate. However, there are few studies on gramdiyne-modified lithium iron phosphate in the prior art, and it is necessary to study how to modify lithium iron phosphate by gramdiyne to improve the charge and discharge specific capacity and good cycle stability of the positive electrode material. Summary of the invention
[0005] In view of the technical problems in the prior art, the object of the present invention is to provide a graphyne-modified lithium iron phosphate positive electrode material and a preparation method thereof, wherein lithium iron phosphate is obtained by a solid phase synthesis method, and then a high-performance positive electrode material is obtained by compounding with graphyne containing oxygen groups. The preparation method of the present invention is simple and convenient for industrial mass production. The prepared positive electrode material has a high charge and discharge specific capacity and good cycle stability in lithium ion batteries.
[0006] To achieve the above objectives, the first objective of the present invention is to provide a method for preparing a composite positive electrode material of graphyne-modified lithium iron phosphate, the method comprising:
[0007] S1: adding a lithium source, iron phosphate, a carbon source and a solvent in a certain proportion into a ball mill mixer and mixing and stirring them evenly to obtain a mixed material;
[0008] S2 placing the mixed material in a sand mill for sand grinding to obtain a mixed slurry;
[0009] S3 spray-drying the mixed slurry to obtain a lithium iron phosphate precursor;
[0010] S4: mixing silyl hexaynylbenzene, dimethylformamide and copper salt solution to obtain a mixed solution, placing the mixed solution in a reaction kettle, and performing a synthesis reaction in an air atmosphere to obtain graphyne containing oxygen groups;
[0011] S5: adding a certain amount of graphyne containing oxygen groups to the lithium iron phosphate precursor, mixing evenly and placing in a high-temperature sintering furnace, calcining in an inert gas to obtain a composite positive electrode material of graphyne-modified lithium iron phosphate.
[0012] Specifically, the lithium source in step S1 is any one or more of lithium carbonate, lithium nitrate, lithium hydroxide and lithium acetate; the carbon source is any one or more of sucrose, glucose, starch and polyethylene glycol.
[0013] Specifically, the amount of the solvent used in step S1 is 5 to 30 ml; the solvent is ethylene glycol or deionized water; the mass of the phosphorus source is 0.01 mol; the mass of the iron source is 0.01 to 1 mol, and the mass of the carbon source is 0.01 to 3 g; the molar ratio of lithium in the lithium source to iron in the iron source is (1.01 to 1.1): 1; and the solid content of the mixed material is 20 to 80%.
[0014] Specifically, the water content of the lithium iron phosphate precursor material in step S3 is ≤2%.
[0015] Specifically, in the mixed solution in step S4, the mass ratio of silylhexynylbenzene to copper salt is 1:(0.05-0.3).
[0016] Specifically, the structural formula of the silylhexynylbenzene in step S4 is
[0017] Specifically, the copper salt catalyst in step S4 is any one or more of CuCl, CuSO4, CuCl2, Cu(NO3)2; and the reaction temperature of the synthesis reaction in step S4 is 60-100°C.
[0018] Specifically, the mass ratio of the oxygen-containing group-containing graphyne to the lithium iron phosphate precursor in step S5 is (0.1-10):100.
[0019] Specifically, the calcination treatment in step S5 is performed at a temperature of 600 to 780° C. and for a time of 2 to 10 hours; the inert gas is any one or more of argon, nitrogen, helium or hydrogen.
[0020] The second object of the present invention is to provide a composite positive electrode material of graphyne-modified lithium iron phosphate prepared by the above-mentioned preparation method.
[0021] Compared with the prior art, the beneficial effects of the present invention include:
[0022] (1) The present invention uses oxygen-containing graphyne to modify lithium iron phosphate. Due to the oxygen-containing groups evenly distributed on the surface of graphyne, the anchoring effect on lithium iron phosphate is enhanced. After ball milling and mixing, the uniformity of dispersion of lithium iron phosphate and graphyne is improved. The lithium iron phosphate is evenly dispersed on the graphyne conductive matrix, which is conducive to forming a uniform conductive network.
[0023] (2) The present invention uses high-temperature calcination to tightly combine Graphene with lithium iron phosphate. Since Graphene has good electrical conductivity, it can effectively enhance the electronic conduction and lithium ion diffusion capacity of the material. The composite positive electrode material prepared by the present invention is applied to lithium batteries, and exhibits excellent electrical conductivity and mass-to-charge transfer efficiency during the battery charge and discharge process, significantly improving the charge and discharge specific capacity and cycle stability of lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the X-ray diffraction pattern of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention.
[0025] Figure 2 This is the X-ray photoelectron spectrum of the graphyne material prepared in Example 1 of the present invention.
[0026] Figure 3 This is a transmission electron microscope image of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention.
[0027] Figure 4 This is the infrared spectrum of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention.
[0028] Figure 5 The cycle performance diagram of the composite positive electrode material b1 prepared in comparative example 1 of the present invention and the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in example 1 when applied in the positive electrode of a lithium-ion battery. DETAILED DESCRIPTION
[0029] The following will combine the contents in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used in this specification have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not used to limit the present invention. The term "and / or" used in this specification includes any and all combinations of one or more related listed items. It should be understood that, unless otherwise specified, various raw materials in the present invention can be obtained commercially.
[0031] Example 1
[0032] S1: Add 2.2 g lithium carbonate, 3.58 g iron phosphate, 0.2 g sucrose and 10 ml ethylene glycol into a ball mill and stir for 30 min to obtain a mixed material a1.
[0033] S2: placing the mixed material a1 in a sand mill for sand grinding, the sand mill speed is 2000r / min, the sand grinding time is 3h, and a mixed slurry a1 is obtained;
[0034] S3 spray-drying the mixed slurry a1 to obtain a lithium iron phosphate precursor a1, wherein the water content of the lithium iron phosphate precursor a1 is 2%;
[0035] S4: 100 mg of silylhexynylbenzene, 12 ml of N,N-dimethylformamide and 20 mg of CuCl are mixed to obtain a mixed solution a1, and the mixed solution a1 is placed in a reaction kettle, and the synthesis reaction is carried out at 100° C. in an air atmosphere for 48 hours to obtain graphyne a1 containing oxygen groups;
[0036] S5: Add 1 g of oxygen-containing graphyne a1 to 10 g of lithium iron phosphate precursor a1 and dry mix them. After mixing evenly, place them in a high-temperature sintering furnace under an argon atmosphere. The calcination temperature is 700°C and the calcination time is 6 hours to obtain the graphyne-modified lithium iron phosphate composite positive electrode material a1 prepared in Example 1.
[0037] Example 2
[0038] S1: Add 0.71 g lithium nitrate, 3.58 g iron phosphate, 0.36 g glucose and 12 ml ethylene glycol solvent into a ball mill and stir for 30 min to mix well to obtain a mixed material a2.
[0039] S2: placing the mixed material a2 in a sand mill for sand grinding at a speed of 2000 r / min for 3 h to obtain a mixed slurry a2;
[0040] S3 spray-drying the mixed slurry a2 to obtain a lithium iron phosphate precursor a2, wherein the water content of the lithium iron phosphate precursor a2 is 1.5%;
[0041] S4: 100 mg of silyl hexaynylbenzene, 12 ml of N, N-dimethylformamide and 10 mg of CuCl2 are mixed to obtain a mixed solution a2, and the mixed solution a2 is placed in a reaction kettle, and the synthesis reaction is carried out at 100° C. in an air atmosphere for 72 hours to obtain graphyne a2 containing oxygen groups;
[0042] S5: Add 0.1 g of oxygen-containing graphyne a2 to 10 g of lithium iron phosphate precursor a2 for dry mixing. After mixing evenly, place in a high-temperature sintering furnace under a helium atmosphere at a calcination temperature of 780°C and a calcination time of 8 h to obtain the graphyne-modified lithium iron phosphate composite positive electrode material a2 prepared in Example 2.
[0043] Example 3
[0044] S1: Add 0.42 g lithium hydroxide, 3.6 g iron phosphate, 0.37 g starch and 10 ml ethylene glycol into a ball mill and stir for 30 min to obtain a mixed material a3.
[0045] S2: placing the mixed material a3 in a sand mill for sand grinding, the sand mill speed is 2000r / min, the sand grinding time is 3h, and a mixed slurry a3 is obtained;
[0046] S3 spray-drying the mixed slurry a3 to obtain a lithium iron phosphate precursor a3, wherein the water content of the lithium iron phosphate precursor a3 is 1.8%;
[0047] S4: 100 mg of silyl hexaynylbenzene, 12 ml of N, N-dimethylformamide and 10 mg of CuSO4 are mixed to obtain a mixed solution a3, and the mixed solution a3 is placed in a reaction kettle, and the synthesis reaction is carried out at 100° C. in an air atmosphere for 24 hours to obtain graphyne a3 containing oxygen groups;
[0048] S5: Add 0.5 g of oxygen-containing graphyne a3 to 10 g of lithium iron phosphate precursor a2 and dry mix them. After mixing evenly, place them in a high-temperature sintering furnace under a nitrogen atmosphere. The calcination temperature is 650°C and the calcination time is 4 hours to obtain the graphyne-modified lithium iron phosphate composite positive electrode material a3 prepared in Example 3.
[0049] Example 4
[0050] S1: Add 0.7 g lithium acetate, 3.6 g iron phosphate, 0.7 g polyethylene glycol and 10 ml deionized water into a ball mill and stir for 30 min to obtain a mixed material a4.
[0051] S2: placing the mixed material a4 in a sand mill for sand milling, the sand mill speed is 2000r / min, the sand milling time is 3h, and a mixed slurry a4 is obtained;
[0052] S3 spray-drying the mixed slurry a4 to obtain a lithium iron phosphate precursor a3, wherein the water content of the lithium iron phosphate precursor a4 is 1.3%;
[0053] S4: 100 mg of silyl hexaynylbenzene, 12 ml of N, N-dimethylformamide and 15 mg of Cu(NO3)2 are mixed to obtain a mixed solution a4, and the mixed solution a4 is placed in a reaction kettle, and the synthesis reaction is carried out at 100°C in an air atmosphere for 50 hours to obtain graphyne a4 containing oxygen groups;
[0054] S5: Add 0.8 g of oxygen-containing graphyne a4 to 10 g of lithium iron phosphate precursor a4 for dry mixing. After mixing evenly, place in a high-temperature sintering furnace under a hydrogen atmosphere at a calcination temperature of 600°C and a calcination time of 2 h to obtain the graphyne-modified lithium iron phosphate composite positive electrode material a4 prepared in Example 4.
[0055] Comparative Example 1
[0056] The difference between Comparative Example 1 and Example 1 is that the lithium iron phosphate is not modified by graphyne.
[0057] S1: Add 2.2 g lithium carbonate, 3.58 g iron phosphate, 0.2 g sucrose and 10 ml ethylene glycol into a ball mill and stir for 30 min to obtain a mixture b1.
[0058] S2: placing the mixed material b1 in a sand mill for sand grinding at a speed of 2000 r / min for a sand grinding time of 3 h to obtain a mixed slurry b1;
[0059] S3 spray-drying the mixed slurry b1 to obtain a lithium iron phosphate precursor b1, wherein the water content of the lithium iron phosphate precursor b1 is 2%;
[0060] S5 was placed in a high-temperature sintering furnace in an argon atmosphere after adding 10 g of lithium iron phosphate precursor. The calcination temperature was 700° C. and the calcination time was 6 h to obtain the lithium iron phosphate composite positive electrode material b1 prepared in Comparative Example 1.
[0061] Performance Characterization
[0062] The composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 was subjected to X-ray diffraction test, X-ray photoelectron spectroscopy test, transmission electron microscopy test and infrared spectroscopy test respectively. Figure 1 This is the X-ray diffraction pattern of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention. Figure 2 This is an X-ray photoelectron spectrum of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention. Figure 3 This is a transmission electron microscope image of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention. Figure 4 This is the infrared spectrum of the composite positive electrode material a1 of graphyne-modified lithium iron phosphate prepared in Example 1 of the present invention.
[0063] from Figure 1 It can be seen that the position of the diffraction peak is completely consistent with the standard spectrum of lithium iron phosphate (JCPDSFIlE40-1499), and there is no diffraction peak of impurities, indicating that the main phase of the final product is composed of well-crystallized lithium iron phosphate, and there are no other impurity peaks. Figure 2 This is the X-ray photoelectron spectrum of the graphyne material prepared in Example 1. It can be seen from the figure that the synthesized graphyne is mainly composed of carbon, with a small amount of O and Cl, and no copper element is detected, indicating that copper only serves as a catalyst, and the synthesized graphyne does not contain copper. It can be clearly seen that lithium iron phosphate is uniformly dispersed on the graphyne conductive matrix containing oxygen groups, forming a uniform conductive network with a dense surface, uniform particle size, and a small particle size. Figure 4 It can be seen that the composite material contains the chemical structure of CO groups.
[0064] Electrochemical performance test
[0065] The electrochemical performance test of the composite positive electrode materials provided in Examples 1-4 and Comparative Example 1 was carried out, and the specific method is as follows:
[0066] A button half-cell was assembled using the composite positive electrode material to be tested: the composite positive electrode material to be tested, a conductive agent (conductive carbon black SP), and a binder (polyvinylidene fluoride, PVDF) were mixed, and then a solvent N-methylpyrrolidone (NMP) was added for homogenization to obtain a slurry; the slurry was then coated on a carbon-coated aluminum foil to obtain a pole piece; a lithium sheet was used as a counter electrode pole piece, and the electrolyte LB-461 was used to assemble the button half-cell in a glove box.
[0067] After the button cell was assembled, its electrochemical performance was tested on a Blue Power Battery Test System (CT2001A) at room temperature of 25°C, and the charge and discharge test was performed at a rate of 1C.
[0068] The electrochemical performance test results of the lithium iron phosphate composite positive electrode materials provided in Examples 1-4 and Comparative Example 1 in lithium batteries are shown in Table 1:
[0069] Table 1
[0070]
[0071] Please refer to Figure 5 , Figure 5 The cycle performance diagram of the composite positive electrode material b1 prepared in comparative example 1 of the present invention and the composite positive electrode material a1 of Graphene modified lithium iron phosphate prepared in Example 1 applied to the positive electrode of a lithium ion battery. Figure 5 It can be seen from the performance data that in the preparation method provided by the present invention, through the synergistic effect of the composite of Graphene containing oxygen groups and lithium iron phosphate, the composite positive electrode material has excellent electrochemical properties, especially in terms of charge and discharge specific capacity and cycle stability. It shows excellent conductivity and mass-to-charge transfer efficiency during the battery charge and discharge process, and significantly improves the charge and discharge specific capacity and cycle stability of the lithium battery. It is significantly higher than the unmodified lithium iron phosphate positive electrode material. The preparation method of the present invention is simple, safe and reliable, and the process conditions are easy to control.
[0072] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention. Therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive. The scope of the present invention is defined by the attached claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention. Any figure mark in the claims should not be regarded as limiting the claims involved.
[0073] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing a composite positive electrode material of Graphene-modified lithium iron phosphate, characterized in that: The preparation method comprises: S1: adding a lithium source, iron phosphate, a carbon source and a solvent in a certain proportion into a ball mill mixer and mixing and stirring them evenly to obtain a mixed material; S2 placing the mixed material in a sand mill for sand grinding to obtain a mixed slurry; S3 spray-drying the mixed slurry to obtain a lithium iron phosphate precursor; S4: mixing silyl hexaynylbenzene, dimethylformamide and copper salt to obtain a mixed solution, placing the mixed solution in a reaction kettle, and performing a synthesis reaction in an air atmosphere to obtain graphene containing oxygen groups; S5: adding a certain amount of graphyne containing oxygen groups to the lithium iron phosphate precursor, mixing evenly and placing in a high-temperature sintering furnace, calcining in an inert gas to obtain a composite positive electrode material of graphyne-modified lithium iron phosphate.
2. The preparation method according to claim 1, characterized in that: In step S1, the lithium source is any one or more of lithium carbonate, lithium nitrate, lithium hydroxide and lithium acetate; the carbon source is any one or more of sucrose, glucose, starch and polyethylene glycol.
3. The preparation method according to claim 1, characterized in that: The amount of the solvent used in step S1 is 5 to 30 ml; the solvent is ethylene glycol or deionized water; the mass of the phosphorus source is 0.01 mol; the mass of the iron source is 0.01 to 1 mol, and the mass of the carbon source is 0.01 to 3 g; the molar ratio of lithium in the lithium source to iron in the iron source is (1.01 to 1.1): 1; and the solid content of the mixed material is 20 to 80%.
4. The preparation method according to claim 1, characterized in that: The water content of the lithium iron phosphate precursor material in step S3 is ≤2%.
5. The preparation method according to claim 1, characterized in that: In the mixed solution in step S4, the mass ratio of silylhexynylbenzene to copper salt is 1:(0.05-0.3).
6. The preparation method according to claim 1, characterized in that: The structural formula of the silyl hexaynylbenzene in step S4 is 7. The preparation method according to claim 1, characterized in that: The copper salt catalyst in step S4 is any one or more of CuCl, CuSO4, CuCl2, Cu(NO3)2; the reaction temperature of the synthesis reaction is 60-100°C.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the oxygen-containing group-containing graphyne to the lithium iron phosphate precursor in step S5 is (0.1-10):
100.
9. The preparation method according to claim 1, characterized in that: The calcination treatment in step S5 is carried out at a temperature of 600 to 78° C. and for a time of 2 to 10 hours; the inert gas is any one or more of argon, nitrogen, helium or hydrogen.
10. A composite positive electrode material of graphyne-modified lithium iron phosphate prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of graphene / lithium iron phosphate composite material
CN105932255A
Composite graphdiyne modified layered oxide material, preparation method thereof, positive plate and sodium ion battery
CN115832314A
Composite coated modified lithium manganese iron phosphate positive electrode material and preparation method thereof
CN116666574A